2011
DOI: 10.1111/j.1600-048x.2010.05208.x
|View full text |Cite
|
Sign up to set email alerts
|

The price of insulation: costs and benefits of feather delivery to nests for male tree swallows Tachycineta bicolor

Abstract: Many species of birds line their nests with feathers, and it has been hypothesized that this functions to provide a thermally stable microenvironment for the development of eggs and nestlings. Feathers in the nest may also function as a mechanism for parasite control, providing a physical barrier that protects nestlings from ectoparasites. We tested these hypotheses by performing a feather removal and addition experiment in tree swallows Tachycineta bicolor, a species wellknown for lining their nests with feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 41 publications
2
57
0
Order By: Relevance
“…However, it is prudent to acknowledge that nest materials can have multiple functions and that aromatic plant materials play an important role in the process of sexual selection in European starlings and other species (Fauth et al, 1991;Gwinner, 1997;Gwinner et al, 2000;Brouwer and Komdeur, 2004). Meanwhile, feathers, which are thought by some to be incorporated into nests to provide a physical barrier between nestlings and ectoparasites instead appear to create a suitable microclimate for offspring development as reported primarily in tree swallows and less commonly in other species (Winkler, 1993;Lombardo et al, 1995;Dawson, 2004;Liljesthröm et al, 2009;Stephenson et al, 2009;Dawson et al, 2011). This suggests that nesting materials do indeed simultaneously serve multiple functions when used by blue and great tits (reviewed by Toft, 1991;Dubiec et al, 2013;Mainwaring et al, 2014b) and that in addition to repelling parasites and pathogens, and acting as sexual signals during courtship, nesting materials may also serve to create optimal environmental conditions for offspring growth and development.…”
Section: Parasite Avoidancementioning
confidence: 99%
See 2 more Smart Citations
“…However, it is prudent to acknowledge that nest materials can have multiple functions and that aromatic plant materials play an important role in the process of sexual selection in European starlings and other species (Fauth et al, 1991;Gwinner, 1997;Gwinner et al, 2000;Brouwer and Komdeur, 2004). Meanwhile, feathers, which are thought by some to be incorporated into nests to provide a physical barrier between nestlings and ectoparasites instead appear to create a suitable microclimate for offspring development as reported primarily in tree swallows and less commonly in other species (Winkler, 1993;Lombardo et al, 1995;Dawson, 2004;Liljesthröm et al, 2009;Stephenson et al, 2009;Dawson et al, 2011). This suggests that nesting materials do indeed simultaneously serve multiple functions when used by blue and great tits (reviewed by Toft, 1991;Dubiec et al, 2013;Mainwaring et al, 2014b) and that in addition to repelling parasites and pathogens, and acting as sexual signals during courtship, nesting materials may also serve to create optimal environmental conditions for offspring growth and development.…”
Section: Parasite Avoidancementioning
confidence: 99%
“…It was then that the seminal paper by Hamilton and Zuk (1982) reported that the elaborate displays of North American birds evolved as a direct consequence of parasitemediated sexual selection, which highlighted the considerable impacts that parasites have on their avian hosts. Accordingly, empirical studies have since shown that parasites are detrimental to their avian hosts by reducing their survival and reproductive success (e.g., Møller, 1990bMøller, , 1993Burtt et al, 1991; reviewed by Loye and Zuk, 1991;Richner et al, 1993;de Lope et al, 1993;Oppliger et al, 1994;Clayton and Moore, 1997;Richner, 1997, 1999;Merino et al, 2000;Proctor, 2003). In great tits, for example, experimental pairs that had hen fleas (Ceratophyllus gallinae) added to their nests fledged fewer and poorer quality nestlings than control pairs that had hen fleas eliminated from their nests (Richner et al, 1993).…”
Section: Parasite Avoidancementioning
confidence: 99%
See 1 more Smart Citation
“…Parasites also affect neonatal birds by reducing body mass (Chapman 1973;Richner et al 1993;Wiebe 2009), length of flight feathers (Chapman 1973), levels ofhaematocrit and/or haemoglobin (Chapman 1973;Richner et al 1993;Hannam 2006), and survival to fledging (Richner et al 1993 ( Gentes et al 2007;Dawson et al 2011;Pigeon et al 2013;Harriman et al 2014). While these studies have suggested negative consequences of parasitism, some have found no effect of ectoparasites on nestlings.…”
Section: Introductionmentioning
confidence: 99%
“…offspring have observed what appear to be negative consequences of parasitism (Chapman 1973;Richner et al 1993;Hannam 2006;O'Brien & Dawson 2008;Dawson et al 2011;Pigeon et al 2013;Harriman et al 2014); others have reported no effect of ectoparasites on nestlings (Roby et al 1992;Johnson & Albrecht 1993;Thomas & Shutler 2001;Gentes et al 2007;Streby et al 2009). Meanwhile, studies of parental effort in relation to nest ectoparasites have also been equivocal, with some finding that one or both parents increase their energy expenditure when their nestlings are parasitized (Christe et al 1996a;Christe et al 1996b;Thomas & Shutler 2001;Tripet et al 2002), some finding a decrease in parental energy expenditure (M0ller 1994; M0ller et al 1994), and others finding no change (Rogers et al 1991;M0ller 1994;Saino et al 1998;O'Brien & Dawson 2008).…”
Section: What Influences Resource Allocation By Avian Parents?mentioning
confidence: 99%